Base-catalyzed stereoselective hydrophenoxylation and hydrothiolation of hexafluorobutyne. Issue 13 (26th March 2020) - Bo, Zhao; Ji-Jun, Zeng; Sheng, Han; Dong-Huai, Tu; Jiang-Wei, Li; Wei, Zhang; Jian, Lu
Graphical abstract: Highlights: Two-phase reaction. Mild reaction conditions. High Z selectivity. 100% Atom utilization. Abstract: Novel base-catalyzed hydrophenoxylation and hydrothiolation of hexafluorobutyne are described. By using an easily available base, a variety of vinyl ethers as well as sulfides are prepared at room temperature through two-phase nucleophilic addition reaction. Mechanistic study revealed that the stereoselectivity of vinyl ethers might depend on frontier orbital interaction under kinetic control.